Firm-specific antecedents affecting product diversification: evidence from India. Issue 3 (3rd July 2021) - Thakur, Anu; Bhatia, Aparna
Abstract: The main purpose of this paper is to introduce what affects the firm to diversify. This paper is based on an empirical analysis of a sample of 453 manufacturing companies in India. Jacquemin-Berry Entropy-Index measure has been used to measure diversification; whereas to determine the factors affecting diversification strategy, Panel Tobit Regression Analysis has been applied. The research findings indicate that firm-specific antecedents influence the decision to diversify. Corporate managers should follow a prudent behaviour while adopting strategic planning for the growth of the company. Managers should have to conduct proper statistical analyses to find out a firm's optimal level of corporate diversification for maximising the firm performance.